The prevalence of depression and its associated factors among married female diabetic patients in Kuantan, Pahang - Md Aris, Mohd Aznan; Tan, Kui Foung; Mohd Rus, Razman (2021)
Depression is reported to affect more women than men in Malaysia. The prevalence of depression among Type 2 Diabetes Mellitus (T2DM) patients ranged 11.5% to 12.6%. The objective of this study was to determine the prevalence of depression and its associated factors among married female diabetic patients attending primary care clinics.